ESCALATION IN STUDENTS’ SCIENCE PROCESS SKILLS ON CHAPTER WAVE VIBRATION AND SOUND THROUGH GUIDED INQUIRY LEARNING MODEL - Winarti Winarti Dr. M.Pd.Si.; Mia Permata Sari (Journal of Teaching and Learning Physics, 2020)
This study aims to determine: (1) the effect of guided inquiry models on students' science process skills, (2) improvement of skills the science process of students with learning inquiry models, This research is a quasi-experimental study with non-equivalent control group design. Data collection techniques used were test and non-test. The instruments in this study were a pretest-posttest cognitive ability test sheet, student worksheets and an observation sheet for science process skills. The data analysis technique used is non-parametric statistics with the Mann Whitney U test, Normalized Gain (N-Gain) and descriptive analysis. The results of this study are that (1) Physics learning using guided inquiry learning models influences the cognitive abilities of students with a significance level (sig. 2-tailed) of 0.013. (2) Physics learning using guided inquiry learning models can improve students' cognitive abilities with an average value of n-gain of 0.701 which is included in the high criteria. Keywords: Guided Inquiry, Science Process Skills, Cognitive Skills, Wave Vibration and Sound.